Implementation of the Hazard Identification, Risk Assessment and Risk Control (HIRARC) Method on Erection Girder Work of South Japek II Toll Road Construction Project Package 3 - Bayu Aninditya; Dwi Dinariana; Fitri Suryani (Pusat Publikasi Nusantara, 2023)
The development of infrastructure is progressing rapidly, particularly for National Strategic Projects, such as the construction of the Jakarta-Cikampek Toll Road (Japek) South II Package 3, which is currently in progress. This toll road project also includes the construction of several interchanges that utilize girders in the process. The project commenced during a challenging time when Indonesia was facing the adverse effects of the Covid-19 pandemic, adding an additional obstacle to infrastructure work. Girder Erection Work, in particular, has recorded various types of accidents over the past few years. In response, the Ministry of Public Works and Public Housing has issued Ministerial Regulation No. 10 of 2021, which provides guidelines for Construction Safety Management Systems (SMKK). By employing the Hazard Identification, Risk Assessment, and Risk Control (HIRARC) method, it is anticipated that construction practitioners can effectively manage risks and reduce workplace accidents in this project. Additionally, the Probability Impact Matrix (PIM) will be utilized to identify the most likely hazards and risks that could significantly impact the project's implementation in the event of an accident. In this study, out of the 57 variables validated by experts, the respondents identified 17 risks classified as high-risk and determined 8 main/dominant risks in the girder erection work of the Jakarta-Cikampek Toll Road Japek South II Package 3 Project. Subsequently, control measures and mitigations are planned for these 8 main risks.